Avaliação em educação física escolar: um olhar para os aspectos sociais e culturais - Pilatti, Angela Cristina Ribeiro (2024)
This investigation focused on the relationships between social and cultural aspects and students' learning in school Physical Education. In this way, we sought to understand how this relationship is perceived during the evaluation process. To this end, qualitative research was carried out with teachers and school coordinators from the Municipal Education Network (SEMED) in the municipality of Guaraniaçu, Paraná. Data collection took place through individual interviews during the teachers' activity hours and through a script with questions about the conceptions, objectives, strategies and main difficulties when evaluating student learning. In the intertwining of situations present at school and in Physical Education classes, the main difficulties highlighted were associated with the lack of specific training, the need for support to assist in transposing the subjectivities present in the assessment and bureaucratic demands. From this, it was observed the need to deepen debates on the topic with teachers and municipal management, which resulted in changes in the municipal education guiding documents, pointing out the need to consider the influences of students' social and cultural conditions in the evaluation process, as well as in specific training provided by the Municipal Department of Education for the second half of 2024 addressing the topic. Carrying out this study revealed necessary notes for carrying out assessments that go beyond bureaucratic impositions and expand perceptions about students' learning and development beyond the classification windows.